Characterization of the Recommendations in the Choosing Wisely Initiative. (July 2019) - Corrigan, Kelsey; Aksenov, Leonid; Paul, Alexandra; Sharif-Askary, Banafsheh; Agarwal, Sarvesh; Kamal, Arif
Choosing Wisely is a comprehensive set of recommendations that guides clinicians and patients away from low-value services. The recommendations were reviewed to investigate their breadth and limitations. The authors performed an abstraction of all Choosing Wisely recommendations between March 1 and May 27, 2016. Descriptive statistics were used to characterize various topics found in the recommendations. Of the 461 Choosing Wisely recommendations, 48% targeted workup studies, 26% non–medication management, 20% medication management, and 6% disease prevention. The most commonly targeted medical issues were coronary artery disease (9%), antibiotics overuse (8%), back pain (6%), breast cancer (5%), and prostate cancer (4%). A limited focus was found on disease prevention and a lack of alignment with health care quality measures. Characterization of Choosing Wisely revealed a comprehensive set of recommendations that addresses low-value care across many specialties. Ultimately, this study provides guidance for promoting the creation and implementation of more patient-centered, representative recommendations.